Alopecia universalis unresponsive to treatment with tofacinitib: report of a case with a brief review of the literature - (:unkn) unknown (My University, 2017)
Janus kinase inhibitors are emerging treatment alternatives in various immune-mediated diseases including alopecia universalis. Herein, we report a patient with psoriasis and alopecia universalis in whom treatment with tofacitinib led to remission of psoriasis without improvement in alopecia universalis. Despite the promising potential in alopecia areata treatment, research evaluating the efficacy of different Janus kinase inhibitors and possible prognostic factors related with a more favorable response are warranted.
Keywords: Humans; Male; Young Adult; Psoriasis; Treatment Failure; Piperidines; Pyrimidines; Pyrroles; Alopecia Areata; Janus Kinase Inhibitors